Penerapan Model Pembelajaran Problem-Based Learning untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Pendidikan Pancasila di Kelas IV SDN 25 Ampenan - Mulyadi, Firdha Jasmine Mulyadi; Farmasari, Santi; Rosidi, Ahyar (Mataram University, 2025)
This study aims to improve students’ learning outcomes in the Pancasila Education subject through the implementation of the Problem-Based Learning (PBL) model in fourth-grade students at SDN 25 Ampenan. The research employed a Classroom Action Research (CAR) design using the Kemmis and McTaggart model, conducted in two cycles involving 32 students. Data collection techniques included observation, tests, and documentation. The results showed that the implementation of the PBL model significantly improved students’ learning outcomes. In the pre-cycle stage, the students’ average score was 58.75, with a classical mastery level of 31.25%. After the first cycle, the average score increased to 72.18, with a mastery level of 65.62%. In the second cycle, students’ learning outcomes improved further, reaching an average score of 85.31 and a mastery level of 90.62%. The application of the PBL model also enhanced students’ engagement in the learning process, making them more active in discussions and problem-solving activities. Therefore, the Problem-Based Learning (PBL) model is proven effective in improving students’ learning outcomes and critical thinking skills. This model is recommended as an innovative alternative for teaching Pancasila Education.